Continuous flow microfluidic cell inactivation with the use of insulating micropillars for multiple electroporation zones. Issue 18 (13th June 2019) - Pudasaini, Sanam; Perera, A T K; Das, Dhiman; Ng, Sum Huan; Yang, Chun
Abstract: Electroporation is a powerful tool for inactivating cells and transfecting biological cells and has applications in biology, genetic engineering, medicine, environment, and many others. We report a new continuous flow device embedded with insulating micropillars to achieve better performance of cell inactivation. The use of micropillars creates multiple electroporation zones with enhanced local electric field strengths. Using a model solution of Saccharomyces cerevisiae, we examined the inactivation performance of the device under various applied electric voltages and flow rates. Results from the numerical simulations and experiments showed that even with an induced transmembrane potential of 0.58 V, close to 63% of cell inactivation was achieved at a flow rate of 2.5 mL/h. This was higher than the 24% cell inactivation observed for a reference device without micropillars that was subjected to the same conditions.